2013
DOI: 10.1002/ejoc.201300434
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Ring‐Closing/Cross‐Metathesis Approach for the Synthesis of Synargentolide B and Its Stereoisomers

Abstract: The stereoselective syntheses of synargentolide B and its three stereoisomers have been accomplished from L‐(+)‐ and D‐(–)‐diethyl tartrates, D‐ribose, and D‐mannitol as chiral pool starting materials. The key step was a tandem ring‐closing/cross‐metathesis reaction in which lactone formation and fragment coupling were accomplished in one pot. The spectroscopic data of synthetic product 2c were in agreement with those reported for the natural product. Synargentolide B isolated by Rivett et al. and the compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…For this, we turned our attention to the literature on nucleophilic allylation of aldehydes D. Madsen and co-workers thoroughly studied domino elimination-alkylation reactions of methyl iodofuranoside E affording products C directly. The isopropylidene-protected aldehyde D has been allylated using catalytic asymmetric Keck conditions [22] or by using allyl-zinc reagents, [23] but the isopropylidene protective group would implicate acidic deprotection in the final stages of the synthesis, conditions that may be incompatible with the targeted epoxides and aziridines. Apart from zinc-or indium-mediated Barbier additions to aldehyde D, [20,21] examples of Grignard-like allylations on the carbonyl group are scarce.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, we turned our attention to the literature on nucleophilic allylation of aldehydes D. Madsen and co-workers thoroughly studied domino elimination-alkylation reactions of methyl iodofuranoside E affording products C directly. The isopropylidene-protected aldehyde D has been allylated using catalytic asymmetric Keck conditions [22] or by using allyl-zinc reagents, [23] but the isopropylidene protective group would implicate acidic deprotection in the final stages of the synthesis, conditions that may be incompatible with the targeted epoxides and aziridines. Apart from zinc-or indium-mediated Barbier additions to aldehyde D, [20,21] examples of Grignard-like allylations on the carbonyl group are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from zinc-or indium-mediated Barbier additions to aldehyde D, [20,21] examples of Grignard-like allylations on the carbonyl group are scarce. The isopropylidene-protected aldehyde D has been allylated using catalytic asymmetric Keck conditions [22] or by using allyl-zinc reagents, [23] but the isopropylidene protective group would implicate acidic deprotection in the final stages of the synthesis, conditions that may be incompatible with the targeted epoxides and aziridines. We therefore decided to investigate the efficacy of 2,3-di-O-benzyl-2,3-dihydroxy-pent-4-enal (1), readily available according to the literature procedure, [16] as the starting material in our allylation studies.…”
Section: Resultsmentioning
confidence: 99%
“…In 1990, Pereda-Miranda et al reported (6R)-[(5R,6S)-diacetyloxy-(1S,2R)-dihydroxy-3E-heptenyl]-5,6-dihydro-2H-pyran-2-one 1 from the leaves of Mexican plant Hyptis oblongifolia. 8 Recently, Prasad et al 9 and Sabitha et al 10 established the structure of 1 by the total synthesis of four diastereomers, individually. The absolute stereochemistry was confirmed by X-ray crystal structure analysis of the corresponding tetraacetate of 1 by Prasad 11 also reported its total synthesis by using D-ribose and L-ascorbic acid as starting materials.…”
Section: From the South African Plantmentioning
confidence: 99%
“…Some RCM-based syntheses for this compound using both [147,148], synparvolide C 85 [149], and (À)-synrotolide 86 [150] are selected δ-lactones belonging to this group and recently prepared by a RCM reaction as the key step. Metathetic syntheses of lactones 81-86 are shown in Scheme 31.…”
Section: Acrylate-type Ring Closure: Synthesis Of Natural Productsmentioning
confidence: 99%